Fish market infrastructure in Khulna city, Bangladesh (Asian-Australasian Journal of Bioscience and Biotechnology, 2019)
An investigation was carried out on fish market infrastructure of Khulna district to identify the infrastructure facilities of domestic fish market including species traded along with price and also to detect the constraints at different levels of trading recommending possible solutions according to standards. The investigation was conducted from November 2016 to June 2017 in three different markets of Khulna district namely Sandhya Bazar fish market, Aranghata Bypass Bazar fish market and Baikali Bazar fish market. In Khulna, a large number of people are involved in fish marketing. Market infrastructures of Khulna had grown up according to various influencing factors that controls the total system involved. The study was based on observation and field survey. Data were collected through eye observation, questionnaire interviews and focus group discussions. Several number of market agents including wholesalers, retailers were selected for questionnaire interviews and aratdars and fishermen were selected for focused group discussions. It was revealed that the infrastructure facilities were inadequate and poorly maintained. Fish sheds were not enough hygienic to protect the fish from contamination. Surface water drainage system was open and this situation degraded further environmental condition of the markets. Electricity maintenance was not up to the mark and there were no distillation process for the supplied water. This infrastructural condition does not support a hygienic condition for fish marketing to provide edible and quality fish. Total number of freshwater fish species traded in different markets was found 60 including 12 SIS, 34 culture and 14 capture. On the other hand 41 brackish and marine water species were found and 14 crustacean species of which 5 were freshwater prawn, 6 brackish water shrimp and 3 crabs. Therefore domestic market infrastructure is on a developing stage as being controlled by Khulna City Corporation (KCC). Establishment of ice factory, improvement of fish transport facilities, introduction of fish quality control measures were suggested to improve the fish marketing in the study area.Asian Australas. J. Biosci. Biotechnol. 2020, 5 (1), 122-134